Arts to change hearts: lessons learned from six years of arts-based cultural humility workshops with healthcare professionals in northern British Columbia (Canadian Medical Education Journal, 2026)
Introduction: Despite proliferation of concepts like anti-racism, allyship, and Indigenous cultural competency, cultural safety, and cultural humility in Canadian healthcare environments, including medical education, few learning opportunities about these practices attend to ways healthcare professionals and learners feel or orient emotionally to these concepts. Our research examined arts-based, anti-colonial, cultural humility training (rooted in Indigenous ways of knowing and being) to build empathetic sociocultural attunement, awareness about anti-Indigenous racism, and practical skills for cultivating culturally safer healthcare environments.Methods: Along with autoethnographic contemplations from 24+ Indigenous and non-Indigenous workshop facilitators, we collected and analyzed 82 narrative evaluations from 29 workshops with over 600 practicing healthcare professionals. Conducted between 2019 and 2025, these workshops provided cultural safety training anchored in reflective practices informed by art, storytelling, and Indigenous ways of knowing and being.Results: Facilitator reflections and participant evaluations validated that: 1) anti-colonial health humanities hold important and undertheorized potentials in combatting anti-Indigenous racism in healthcare, and 2) friendships and place-based relationships of facilitators inform outcomes of cultural humility and safety training.Conclusion: Developing new arts-based tools and practices that speak to the heart, account for people’s emotionality, and that incorporate Indigenous ways of knowing and being is vital to anyone, especially those in medical education, working to cultivate culturally safer healthcare environments. Strategies developed in our work may inform geographically specific, emotionally attuned, relationship-based, creative, adaptive, and flexible ways to combat anti-Indigenous racism in healthcare.